Butte Paper - Mineral Associations at Butte, Mont. - D. C. Bard; M. H. Gidel (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
These notes are based on the megascopic study of a suite of 2,400 specimens of minerals and ores from the Butte mines, combined with field observations at intervals over a period of several years. The estimate of average vein composition is based on field acquaintance with the veins. It is probably correct in its broader proportions, and should be of use for comparison. Chemical and Mineral Composition of Unoxidized Vein Matter. Per Cent. Oxygen,......48.00—Quartz, rhodonite, rhodochrosite, sericite, kaolinite, barite, calcite, and hübnerite. Silicon,...... 36.O0—Quartz, rhodonite, sericite, kaolinite, and willemite (very rare). Sulphur,.....5.0—Sulphides of iron, zinc, copper, lead, and sulphates of barium and rarely calcium. Iron,.......5.00—Ferric sulphides (pyrite, bornite, chalcopyrite), also in sphalerite, tetrahedrite, and rarely hematite and siderite. Manganese,.... 2.00—Rhodonite, rhodochrosite, and hübnerite. Zinc,.......1.00—Sphalerite, very rare wurtzite and willemite, and tetrahedrite and tennantite. Carbon,......0.50—Rhodochrosite and calcite. Capper,......0.75—Cuprous ( + ) and cupric (—) sulphides. Aluminum,.... 0.50—Sericite and kaolinite. Hydrogen,.... 0.50—Water, sericite, and kaolinite. Potassium,.....0.20—hicite. Lead,....... 0.20—Galena. Arsenic,......0.10—Tennantite and enargite. Barium,......0.10—Barite. Calcium,.....0.10—Fluorite, calcite, and rare gypsum. Antimony,.... 0.02—Tetrahedrite, famatinite, and silver sulphantimonites. Fluorine,.....0.05—Fluorite. Silver,.....1 —Argentite, and sulphantimonites. Tungsten,.... —Hübnerite. Phosphorus, • —Wavellite. Bismuth,' .... 0.05—Sulphide (?) Tellurium,... 1 —Telluride (?) Selenium,.... —Selenide (?) Cadmium,.... —Sulphide (?) Gold,..... —Native and telluride (?)